Automatic activation of self-discrepancies and emotional syndromes: when cognitive structures influence affect - Strauman, T J; Higgins, E T (Journal of personality and social psychology, 1987)
Different types of self-discrepancies are associated with different negative affects. Two studies were conducted to determine whether automatic activation of specific actual-self: self-guide mismatches, as cognitive structures, would induce distinct emotional states. Subjects possessing significant discrepancies between their actual self and either their ideal self-guide (attributes that someone wishes or hopes the person would possess) or their ought self-guide (attributes that someone believes the person has the duty or obligation to possess) responded verbally to an audiotape while "thinking about other people." Study 1 involved two kinds of priming attributes: self-relevant and yoked (another subject's self-relevant attributes). Activating mismatches induced momentary syndromes of dejection (sadness, decreased arousal) in ideal-discrepant subjects but induced agitation (nervousness, increased arousal) in ought-discrepant subjects. In Study 2, subjects were randomized to either self-relevant/nondiscrepant, self-discrepant, or yoked priming. The findings of Study 1 were replicated for the self-discrepant priming condition alone. Results indicate that (a) mismatches constitute cognitive structures and (b) automatic activation of different mismatches via contextual priming induces distinct types of emotional discomfort.